Prevention and Treatment of Early Childhood Caries (ECC) - ., Jeffrey (Journal of Medicine and Health, 2016)
Early Childhood Caries (ECC) is a chronic disease that can be prevented. It commonlyaffects children involving in one or more decayed (with lesions or not) teeth, missing teeth (dueto caries), or teeth with fillings in children aged under 71 months. The disease is sometimesoverlooked, but this condition usually affects the general health of children. Early detection ofEarly Childhood Caries (ECC) can prevent problems which are harmful to children. Therefore,the ECC must be prevented and for teeth that have had dental caries they should be givenproper treatment so as not to worsen and affect the quality of life in children. Prevention of thisdisease is a significant component in any health program to prepare for the optimal basis forthe oral health of children. This condition will become a serious health problem if not handledproperly, and it is a major health problem for health providers throughout the world.Primarypreventive must be initiated since a woman getting pregnant.Keywords: Early Childhood Caries (ECC), prevention, treatment